2015
DOI: 10.1039/c5an00774g
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prototyping of microfluidic devices with integrated wrinkled gold micro-/nano textured electrodes for electrochemical analysis

Abstract: Fully-integrated electro-fluidic systems with micro-/nano-scale features have a wide range of applications in lab-on-a-chip systems used for biosensing, biological sample processing, and environmental monitoring. Rapid prototyping of application-specific electro-fluidic systems is envisioned to facilitate the testing, validation, and market translation of several lab-on-a-chip systems. Towards this goal, we developed a rapid prototyping process for creating wrinkled micro-/nano-textured electrodes on shrink me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…The PDMS channels were then bonded to the PS‐Planar or PS‐AuNP‐Shrunk through wet bonding. [ 63 ] This was done by creating a thin layer of PDMS (10:1) by depositing 400 µL PDMS in a petri dish and spin coating for 30 s at 7000 rpm. The PDMS channel was stamped on the spin coated layer then placed carefully on PS‐Planar or PS‐AuNP‐Shrunk and cured overnight.…”
Section: Reagentsmentioning
confidence: 99%
“…The PDMS channels were then bonded to the PS‐Planar or PS‐AuNP‐Shrunk through wet bonding. [ 63 ] This was done by creating a thin layer of PDMS (10:1) by depositing 400 µL PDMS in a petri dish and spin coating for 30 s at 7000 rpm. The PDMS channel was stamped on the spin coated layer then placed carefully on PS‐Planar or PS‐AuNP‐Shrunk and cured overnight.…”
Section: Reagentsmentioning
confidence: 99%
“…Furthermore, it was higher than those realized by other previously reported methods performed at room temperature 3,12 and, in our case, was attained via much simpler and faster procedures. For this reason, the method introduced in this study can be considered a promising option for certain types of devices requiring relatively low-pressure (∼ 35 kPa) 22 experimental conditions, such as for cell patterning, or when electrodes are integrated in microdevices that must withstand pressures from 125 to 300 kPa 23,24 . Fig.…”
Section: Bond Strength Analysismentioning
confidence: 99%
“…Research in the use of "high surface area" electrodes presents a clever solution to this problem in which one creates a rough micro-and/or nanostructured surface topography that considerably enhances the working electrode's electrochemically active surface area (EASA) relative to its macroscopic footprint. While complex chemical deposition methods to this end have been available for decades (Salvarezza et al, 1990;Gabardo et al, 2015;Sonney et al, 2015), recent research has shown that enhanced EASA can be achieved more simply by heat-shrinking a polymer substrate coated with metal thin film electrodes (Gabardo et al, 2013;Pegan et al, 2013). Fabrication of these shrink electrodes is low-cost and does not require sophisticated equipment or clean-room facilities.…”
Section: Introductionmentioning
confidence: 99%